Investigation of electric ARC plasma between composite Cu–C electrodes - Veklich, A.N.; Boretskij, V.F.; Ivanisik, A.I.; Lebid, A.V.; Fesenko, S.A. (Вопросы атомной науки и техники, 2013)
Plasma of electric arc discharge in air between composite Cu–C electrodes at arc current 3.5 A in the assumption of local thermodynamic equilibrium was investigated. Special electric device for arc ignition was suggested. The radial profiles of temperature in discharge column were obtained by optical emission spectroscopy. The radial profiles of copper density were obtained by laser absorption spectroscopy.